ショウワ キチ ニオケル イッサンカ チッソ ブンシ ミツド ブンプ ノ ロケット カンソク オヨビ 5200Å ホウシャ ノ チジョウ カンソク f. キョクイキ デンリソウ ダイ2カイ キョクイキ ニオケル デンリケン ジキケン ソウゴウ カンソク シンポジウム PART 2 - 岩上, 直幹; イワガミ, ナオモト; 小川, 利紘; オガワ, トシヒロ; 近藤, 豊; コンドウ, ユタカ; IWAGAMI, Naomoto; OGAWA, Toshihiro; KONDO, Yutaka (1980)
P(論文) 昭和基地から打ち上げられたS-210JA-27号機によって,高度72-120kmのNO分子密度分布が,γ(1,O)バンドの共鳴螢光放射率の測定から求められた.得られたNO分子密度分布は静穏時であったにもかかわらず,これまで中低緯度で測定されたものに比べ,高度100km以上で5倍程度,100km以下ではひと桁以上大きい.どの大きなNO分子密度は,前夜あるいはそれ以前にあったじょう乱の影響によるものであると思われる.また昭和基地において,準安定窒素原子N(2^D)の放出する波長5200Å輝線の放射率が,ティルティングフィルタ方式を用いた地上観測によって測定された.観測された5200Å放射の特性は,中緯度夜間の主励起機構である解離再結合よりも降下粒子による直接励起が卓越していることを示している. The nitric oxide density profile between 72 and 120 km was measured with a specially designed ultraviolet radiometer making use of the resonant fluorescence in the γ(1,0) band near 2150 Å aboard a sounding rocket launched at Syowa Station (69°S, 39.6°E) under geomagnetically quiet conditions. The observed nitric oxide density was found to be much larger than those obtained at middle and low latitudes. It can be attributed to the after-effect of particle precipitations during the previous night. The 5200 Å emission from metastable atomic nitrogen, N(^2D), was measured at Syowa Station by the tilting filter method. The characteristic of observed 520 Å emission seems to show the dominance of particle impact excitations rather than dissociative recombination excitation. departmental bulletin paper